2022
DOI: 10.1039/d2ra05558a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of novel sinomenine derivatives as anti-inflammatory and analgesic agent

Abstract: A series of novel sinomenine derivatives were designed and synthesized. Among them, compound 17 showed strong anti-inflammatory and analgesic activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 47 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…Zhou et al found that N-demethyl SIN (30) attenuated neuropathic and inflammatory pain in mice, which was more effective than that of SIN [148]. F. Gao et al reported that SIN derivative 17 (31) significantly inhibited the secretion of the pro-inflammatory factor µnitric oxide in Mouse mononuclear macrophage leukemia cells Raw264.7, with an IC 50 value of 30.28 µM and no cytotoxic effects at concentrations up to 100 µM [149]. E.E.…”
Section: Anti-inflammatory Activity and Analgesic Activity Of Compoun...mentioning
confidence: 99%
“…Zhou et al found that N-demethyl SIN (30) attenuated neuropathic and inflammatory pain in mice, which was more effective than that of SIN [148]. F. Gao et al reported that SIN derivative 17 (31) significantly inhibited the secretion of the pro-inflammatory factor µnitric oxide in Mouse mononuclear macrophage leukemia cells Raw264.7, with an IC 50 value of 30.28 µM and no cytotoxic effects at concentrations up to 100 µM [149]. E.E.…”
Section: Anti-inflammatory Activity and Analgesic Activity Of Compoun...mentioning
confidence: 99%